HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA PASIEN TB DI WILAYAH KERJA PUSKESMAS BENGKURING SAMARINDA - Hesti Prawita Widiastuti; Ayu Listiyo Hati Ningrum; Wiyadi Wiyadi (Poltekkes Kemenkes Kalimantan Timur, 2022)
Family support is one of the social support that could improve TB patients’ medication adherence. This research is determined to find out the relation between family support with TB patients’ medication adherence in work area of Bengkuring Civic Health Centre Samarinda. A quantitative research with cross sectional research design. Population of 70 people. Sample of 70 people using total sampling method because of the total sample is less than 100 respondents. Instrument that used in this research is standard questionnaire of family support according to Nursalam and questionnaire of Medication Adherence Morinsky Medication Adherence Scale (MMAS). Questionnaires were given door to door and during the medication pickup in Civic Health Centre, and followed by filling in the questionnaire. Furthermore, the data is analyzed in univariate and bivariate manner with Chi Square test. Scores obtained from the variable of family support and medication adherence with p= 0,001, the result of p value < 0,05 (Sig. 95%). Therefore, Ho is rejected and Ha is accepted, thus, there is a relation between family support and TB Patients’ medication adherence. There is a relation between family support with TB Patients’ medication adherence. The next researchers are suggested to do a random sampling and analyzing respondents’ characteristics such as age and education that could affect the result.